ИЗОМЕТРИИ LOG-АЛГЕБР И ИХ ВЗАИМОСВЯЗЬ С РАЗЛИЧНЫМИ ПРОСТРАНСТВАМИ ИНТЕГРИРУЕМЫХ ФУНКЦИЙ, ПОСТРОЕННЫХ ОТНОСИТЕЛЬНО Σ-КОНЕЧНЫХ МЕР - Абдуллаев, Р.З.; Абдимуратов, М.; Узакбаева, Ф. (SCIENCE and SOCIETY, 2023)
The paper establishes a connection between log-algebras and various spaces of integrable functions constructed with respect to σ-finite measures. We also study isometries of log-algebras on von Neumann algebras of type I2.
Keywords: isometries; log-algebras; σ-finite measures; Arens algebras; F-spaces